AB0348 Risk of falling is equivalent between patients with rheumatoid arthritis and healthy individuals -the tomorrow study-. (23rd January 2014) - Sugioka, Y.; Koike, T.; Mamoto, K.; Okano, T.; Tada, M.; Wakitani, S.; Nakamura, H.
Abstract : Background: Patients with rheumatoid arthritis (RA) who have muscle weakness and stiff or painful joints might be at increased risk of falling. The present study prospectively determines the incidence of falls and their risk factors in patients with RA who participated in the TOMORROW (TO tal M anagement O f R isk factors in R heumatoid arthritis patients to lOW er morbidity and mortality; clinical trial registration number: UMIN000003876) study that was started in 2010. Methods: We evaluated anthropometric parameters, muscle volume, bone density, disease activity, general health status and the occurrence of falls for a period of one year in 202 patients with RA (54% administered with biological agents) and 202 age- and sex-matched healthy volunteers (HV). Results: Among the patients with RA and HV, 18% and 16% respectively reported one or more falls during the previous year.These values did not significantly differ. After adjusting for risk factors of falls such as a history of falls, age, gender, smoking and BMI, multiple logistic regression analysis identified that a history of falls was the most significant parameter associated with falls (odds ratio: 2.71, p<0.001 Table). The RA group also had lower whole muscle volume (37.2 vs. 39.6 kg; p=0.001), leg bone mineral density (0.967 vs. 1.031 mg/cm 3 ; p<0.001) and shorter exercise periods than HV, but none of these were associated with rates of falling. Furthermore, fall risk did not significantly and linearly increase with disease duration, disease activity score and physical status among the patients with RA. Conclusions: We concluded that the fall rate is not higher in patients with RA than in healthy volunteers and that only a history of falls plays a role in increasing the risk of falls. Disclosure of Interest: Y. Sugioka: None Declared, T. Koike Grant/Research support from: Takeda Pharmaceutical, Mitsubishi Tanabe Pharma Corporation, Chugai Pharmaceutical, Eisai, Abbott Japan, Teijin Pharma, Banyu Pharmaceutical and Ono Pharmaceutical, K. Mamoto: None Declared, T. Okano: None Declared, M. Tada: None Declared, S. Wakitani: None Declared, H. Nakamura Grant/Research support from: Chugai Pharmaceutical, Astellas Pharma Inc., Janssen Pharmaceutica, GlaxoSmithKline, Pfizer Inc. and Daiichi Sankyo, INC., Speakers Bureau: Ono Pharmaceutical